The fate of imazapyr herbicide in the soil amended with carbon sorbents - Yavari, S. (Springer Science and Business Media Deutschland GmbH, 2021)
Excessive application of agro-chemicals is a major factor in undesired environmental problems. Imidazolinone herbicides having high activity, leaching potential, and persistence are probable risks to ecosystems. Herbicidesâ stabilization using biochar is an efficient and cheap strategy to protect the environment against their contaminations. The present study aimed to evaluate the effects of biochars produced from oil palm empty fruit bunches (EFB) and rice husk (RH) on imazapyr fate in soil. Initially, the optimized biochars were compared for their sorption-desorption capacities as soil modifiers. The herbicide leaching in the amended soils was investigated by leaching columns. The herbicide photolysis and bio-degradationsâ rates in the media were also evaluated during 70 days. Results indicated that the soil amendment significantly increased soil sorption capacity (up to 2.34-folds) and reduced the herbicide leaching. The lowest percentage of leached herbicide (2.8) and the highest percentage of retained herbicide (97.1) were achieved in EFB biochar-amended soil. The herbicide photo-degradation rate significantly reduced with a half-life of 38.5 days in non-amended soil to 53.3 days in EFB biochar-amended soils. The herbicide bio-degradation, however, increased with the biochars applications. In a conclusion, the optimized biochars have a high potential to protect the environment against herbicides hazards. Â© 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.